Comparative community burden and severity of seasonal and pandemic influenza: results of the Flu Watch cohort study - Hayward, Andrew C.; Fragaszy, Ellen B.; Bermingham, Alison; Wang, Lili; Copas, Andrew; Edmunds, W. John; Ferguson, Neil; Goonetilleke, Nilu; Harvey, Gabrielle; Kovar, Jana; Lim, Megan S.C.; McMichael, Andrew; et al. (Elsevier, 2014)
BACKGROUND: Assessment of the effect of influenza on populations, including risk of infection, illness if infected, illness severity, and consultation rates, is essential to inform future control and prevention. We aimed to compare the community burden and severity of seasonal and pandemic influenza across different age groups and study years and gain insight into the extent to which traditional surveillance underestimates this burden.